Development of a Solidification of Floating Organic Droplet-Based Liquid-Liquid Microextraction Method Utilizing a Schiff Base Ligand for the Determination of Nickel at Trace Levels in Saint John's Wort Tea Infusions by Matrix Matching Calibration Assisted Slotted Quartz Tube-Flame Atomic Absorption Spectroscopy - Atakol, Melike; Akbiyik, Hilal; Atakol, Arda; Yildirim, Vedat; Bakirdere, Sezgin; Atakol, Orhan (TAYLOR & FRANCIS INC, 2025)
A sensitive and economical analytical method involving the solidification of floating organic drop microextraction technique with a dispersive solvent is utilized for extraction and enrichment of nickel in St. John's wort tea infusions. Bis-N,N '-(salicylidene)-1,3-propanediamine was used as the complexing agent. The analyses were done with a slotted quartz tube-flame atomic absorption spectrometer (FAAS). The experimental parameters for the preconcentration procedure were optimized. The developed method provided a 26.5-fold enhanced detection power compared to determination by conventional FAAS. The limits of detection and quantification were 24 and 79 mu g/kg, respectively, within a linear range of 50-500 mu g/kg. The applicability of the method was tested on infusions of two samples of St. John's wort tea. Matrix matching was adopted to eliminate/minimize the interferences on the signal. Spiked experiments in which high recovery values in the range of 89.3-121.4% were obtained indicate the accuracy and validity of the method.
Keywords: Dispersive liquid-liquid microextraction (DLLME); environmental analysis; flame atomic absorption spectrometry (FAAS); green chemistry; herbal tea analysis; PLANTS; SPECTROMETRY; STRATEGY; POLYMER; SAMPLES; METALS; WATER; FAAS; Chemistry